Association of the Effect of Alcohol Consumption on Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH), and Testosterone Hormones in Men: A Systematic Review and Meta-Analysis - Mahmood Moosazadeh; Keyvan Heydari; Kimia Rasouli; Soroush Azari; Mahdi Afshari; Saeed Barzegari; Roja Nikaeen; Maryam Kardan-Souraki; Soghra Khani; Farzaneh Motafeghi; Aref Hoseini (International Journal of Preventive Medicine)
Background: The present study is a systematic review and meta-analysis aiming to investigate the effects of alcohol consumption on male sex hormones in humans. Methods: We conducted searches on PubMed, Scopus, Science Direct, and Google Scholar from June 2020 to June 2022. We included observational studies (cohorts, case-controls, and cross-sectional studies) comparing FSH, LH, or testosterone levels in alcohol consumers versus non-consumers. Subgroup analysis based on alcohol intake levels was conducted to explore potential heterogeneity sources. The meta-analysis was done by STATA version 11. Seventeen studies met the criteria. Results: Combining data from these studies, the standardized mean differences for FSH, LH, and testosterone in alcohol-exposed versus non-exposed groups were −0.00 (95% CI: −0.099–0.099), 0.04 (95% CI: 0.00–0.12), and 0.03 (95% CI: −0.11–0.16), respectively, showing no statistical significance. Subgroup analysis indicated a significant difference in FSH levels between moderate/high and low alcohol consumption groups (−0.04, 95% CI: −0.08 to −0.00). Similarly, compared to non-exposed individuals, testosterone levels differed significantly in groups with moderate (0.22, 95% CI: 0.12–0.32) and low (0.19, 95% CI: 0.04–0.35) alcohol intake. Given the notable alterations observed in testosterone levels among individuals with alcohol use disorder and the associated feedback changes in LH levels, it has been concluded that alcohol overuse should be recognized as a factor with destructive effects. Conclusions: It is suggested that future research includes comprehensive studies to investigate the changes in the hypothalamus-pituitary-testis axis induced by alcohol consumption.